Modern Approaches to the Diagnosis and Treatment of Tonsillopharyngitis (Review of International Guidelines) - Yu.A. Molochek (Zaslavsky O.Yu., 2014)
The article presents an overview of guidelines on the treatment of tonsillopharyngitis in children. Attention is given to the use of nonsteroidal anti-inflammatory drugs (NSAIDs) in this pathology. It is emphasized that the topical application of NSAIDs enables to solve the problem of throat pain relief and improved quality of life in patients with infectious and inflammatory processes in the oropharynx, particularly tonsillopharyngitis of both viral and bacterial origin.